1991
DOI: 10.3354/dao011173
|View full text |Cite
|
Sign up to set email alerts
|

Lumhol-dependent chemiluminescence by hemocytes of two marine bivalves, Ostrea edulis and Crassostrea gigas

Abstract: Microbicidal phagocytic function and oxidative metabolism of the hemocytes of 2 oyster species, Ostrea edulis and Crassostrea gigas, were investigated using a luminol-enhanced chemiluminescence (CL) technique. First, experimental parameters adapted to marine bivalve hemocytes were established on hemolymph pools of C. gigas in order to obtain qualitatively and quantitatively homogeneous samples and so to perform statistically comparable assays. The use of Modified Alsever Solution (MAS) allowed hemocytes to b e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
0
2

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(70 citation statements)
references
References 22 publications
3
65
0
2
Order By: Relevance
“…Two main haemocyte functions can be evaluated using this technique: phagocytosis, which represents probably the most investigated functional aspect of haemocyte activity (Cheng, 1996), and the 'oxidative burst'. Generation of reactive oxygen species at the end of the oxidative burst process has been observed in several bivalves such as C. gigas (Bachère et al, 1991;Greger et al, 1995), C. virginica (Anderson et al, 1992), O. edulis (Hervio et al, 1989;Bachère et al, 1991), M. edulis (Pipe, 1992;Noël et al, 1993) and Mediterranean mussel Mytilus galloprovincialis (Arumugan et al, 2000) but has not been detected in clam species such as R. decussatus (López et al, 1994) and hard shell clam Mercenaria mercenaria (Cheng et al, 1975). Also, production of nitrite oxide, another active oxygen intermediate, has been recently demonstrated in C. gigas (Nakayama and Maruyama, 1998), M. edulis (Ottaviani et al, 1993), M. galloprovincialis (Arumugan et al, 2000) and R. decussatus (Taffala et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Two main haemocyte functions can be evaluated using this technique: phagocytosis, which represents probably the most investigated functional aspect of haemocyte activity (Cheng, 1996), and the 'oxidative burst'. Generation of reactive oxygen species at the end of the oxidative burst process has been observed in several bivalves such as C. gigas (Bachère et al, 1991;Greger et al, 1995), C. virginica (Anderson et al, 1992), O. edulis (Hervio et al, 1989;Bachère et al, 1991), M. edulis (Pipe, 1992;Noël et al, 1993) and Mediterranean mussel Mytilus galloprovincialis (Arumugan et al, 2000) but has not been detected in clam species such as R. decussatus (López et al, 1994) and hard shell clam Mercenaria mercenaria (Cheng et al, 1975). Also, production of nitrite oxide, another active oxygen intermediate, has been recently demonstrated in C. gigas (Nakayama and Maruyama, 1998), M. edulis (Ottaviani et al, 1993), M. galloprovincialis (Arumugan et al, 2000) and R. decussatus (Taffala et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…et al, 1989;Bachere et al, 1991b;Morvan et al, 1994 . The quantification of NBT reduction and the ability of haemocytes to produce ROIs can be considered as functional tests for the evaluation of immune potential at a cellular and organismal level.…”
mentioning
confidence: 99%
“…Ž vertebrate blood cells Roschger et al, 1990 and marine bivalve haemocytes Fisher . and Newell, 1986;Bachere et al, 1991b . Seawater has been widely used for in vitrò assays when marine invertebrate haemocytes functionality is studied because it may provide the haemocytes with cations or other essential elements for their successful stimulation and activity.…”
mentioning
confidence: 99%
“…The gill represents the main interface between aquatic organisms and the external environment. Bivalve mollusk gills are one of the first lines of defense against bacterial infection; it has become increasingly evident that the hemocytes play a central role in the internal defense of bivalves (Pipe, 1990;Bachere et al, 1991;Wang et al, 2012). The upregulation of Mm-LGBP mRNA after Vibrio anguillarum challenge showed that Mm-LGBP plays a pivotal role in antibacterial immunity, further confirming the presence of the LPS recognition and binding site in Mm-LGBP.…”
mentioning
confidence: 60%